2020
DOI: 10.1021/acsami.0c03039
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous Materials Based on Polymeric Salicyl Active Esters as Efficient Adsorbents for Selective Removal of Anionic Dye

Abstract: To increase the performance efficiency and decrease the costs for organic dye wastewater purification, two fibrous adsorbents based on polymeric salicyl active esters were developed by means of a simple two-step approach. For the first time, salicyl-based active ester polymers were electrospun into fibrous membranes and subsequently postmodified with the desired functional groups under simple and mild reaction conditions. The morphology of the produced fibrous adsorbents was characterized by scanning electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 66 publications
0
27
0
Order By: Relevance
“…where K F [(mg/g) (L/mg) 1/n ] is the Freundlich constant where the heterogeneity factor 1/n is employed to predict the adsorption situation of an unfavorable (1 < 1/n), favorable (0 < 1/n < 1), or irreversible (0 < 1/n) situation. 44 Meanwhile, whether the adsorption nature is physical or chemical can be judged from the D−R model, which can be presented as the linear form where β (mol 2 /kJ 2 ) and ε are the D−R isotherm constant and the Polanyi potential, respectively. Meanwhile, ε and the mean free energy E (kJ/mol) are calculated by the equations ε = RT ln(1 + 1/C e ) and E = (1/2 β) 1/2 , respectively, where R (kJ/ mol K) and T (K) are the gas constant and temperature, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…where K F [(mg/g) (L/mg) 1/n ] is the Freundlich constant where the heterogeneity factor 1/n is employed to predict the adsorption situation of an unfavorable (1 < 1/n), favorable (0 < 1/n < 1), or irreversible (0 < 1/n) situation. 44 Meanwhile, whether the adsorption nature is physical or chemical can be judged from the D−R model, which can be presented as the linear form where β (mol 2 /kJ 2 ) and ε are the D−R isotherm constant and the Polanyi potential, respectively. Meanwhile, ε and the mean free energy E (kJ/mol) are calculated by the equations ε = RT ln(1 + 1/C e ) and E = (1/2 β) 1/2 , respectively, where R (kJ/ mol K) and T (K) are the gas constant and temperature, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The Freundlich model hypothesizes the multilayer adsorption owing to the difference of the adsorption energy. The model can be mathematically presented as the linear form where K F [(mg/g) (L/mg) 1/ n ] is the Freundlich constant where the heterogeneity factor 1/ n is employed to predict the adsorption situation of an unfavorable (1 < 1/ n ), favorable (0 < 1/ n < 1), or irreversible (0 < 1/ n ) situation …”
Section: Resultsmentioning
confidence: 99%
“…Self-assembled microgels comprised of poly(N-isopropylacrylamide- co -2-(dimethylamino) ethyl methacrylate) and sodium alginate (SA) have demonstrated a highly pH-sensitive response [ 66 ]. Methyl blue is an anionic hydrophilic dye molecule which has been reported to be adsorbed onto microgel core star ionic covalent organic polymers, polymers, fibrous materials, and cross-linked polymer particles with cavity and ammonium functionalization [ 62 , 67 , 68 , 69 ]. A quartz crystal microbalance (QCM) investigation of the interaction between anionic dyes and the SA/microgel multilayers in the aqueous phase revealed an enhanced electrostatic attraction between the dyes and the microgels deposited on the QCM sensor surface compared to that with SA in the multilayers, which caused the release of microgels from the self-assembled structure and a mass loss ratio of 27.6% [ 66 ].…”
Section: Polyelectrolyte–dye Interactionsmentioning
confidence: 99%
“…The results showed that after four cycles of mass transfer at 60 V, the membrane surface changed to a loose porous network fiber structure which indicated that the membrane is not appropriate for continuous mass transfer at 60 V. Mass transfer activation energy showed that applying higher Electrospinning is the practical method to produce polymer nanofibers that have high porosity, excellent mechanical properties, and high specific surface area to volume ratio. Zhang et al 138 prepared poly(methyl salicylate acrylic ester) (PMSAE) fibers that were modified postpolymerization with the primary amines 4,7,10-trioxa-1,13-tridecanediamine (TTDD) and 3,6,9-triazaundecan-1,11-diamine (TAD) for removing Ni 2+ from wastewater. The adsorption capacity of PMSAE-TTDD and PMSAE-TAD toward Ni 2+ was 3.79 and 3.27 mg•g −1 , respectively.…”
Section: Heavy Metal Detection and Remediationmentioning
confidence: 99%